ANALISIS PERSEBARAN BIDANG TANAH BERDASARKAN PEMANFAATAN TANAH MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (STUDI KASUS : KECAMATAN KEDUNGKANDANG, KOTA MALANG, PROVINSI JAWA TIMUR) - Rico Waskito Putro; Sawitri Subiyanto; Moehammad Awaluddin (Departement Teknik Geodesi Universitas Diponegoro, 2013)
Soil is the main source of well-being and lives of the people, therefore the use of land and optimum utilization of land. Embodiments of use and optimum utilization of land can be done through the preparation of spatial plans that integrate the principles of sustainable development. Harmonizing with the land use plan should be organized in spatial planning so that every area of soil can provide optimal and sustainable benefits and cultivated in an efficient and balanced while respecting the rights of the people, it will be quickly prepared and organized when available land use maps and large-scale land use. In Article 40 of the National Land Agency Regulation No.. 4 of 2006 regulating the duties and Potential of Sub Soil Thematic Section in the Land Office is preparing a survey, mapping, maintenance and development of thematic mapping, soil potential surveys, maintenance of technical equipment and coaching officials computerized land appraiser. Thematic Mapping Section provides Thematic Maps, on the other hand measurements and surveys section provides the Land Registry Map. The second map illustrates the results so far have not shared in the ranks of the Land Office for each component in the making and has a map coordinate system and different scales, so that the information given as a result the data is still partially owned by the Land Office can not provide the information and results maximum, and mapping costs become very large.This study was conducted to obtain accurate results and a thorough map of the distribution of land parcels complete with the land use and land use especially in sub Kedungkandang complete, Malang. Land use in the District Kedungkandang mostly used for agricultural production, better utilization of land for fields registered or not registered or less have the total percentage of 55.87%. As for the land that has not been used has the smallest percentage than others, namely the extent of utilization of 0.10%Keywords: Land Use, Land Affairs, Thematic Maps, GIS.